Fulvestrant and male breast cancer: a pooled analysis - Zagouri, F.; Sergentanis, T.N.; Chrysikos, D.; Dimopoulos, M.-A.; Psaltopoulou, T. (Breast Cancer Research and Treatment, 2015)
Male breast cancer is an uncommon malignancy; little is known regarding hormonal manipulations for tamoxifen-resistant male breast cancer patients. This is the first pooled analysis of the literature to synthesize all available data and to evaluate the efficacy and safety of fulvestrant in male breast cancer. This study was performed in accordance with the PRISMA guidelines. All studies that examined the efficacy of fulvestrant in male breast cancer, regardless of sample size, were considered eligible. The search strategy retrieved 31 articles; of these, five articles were eligible (23 patients) for this pooled analysis. The mean age of the study sample was 63.1 years. Adjuvant hormonal treatment was administered in 87.5 % of cases. Fulvestrant was given as first or second line in 40 % of patients, while as third line or beyond in 60 % of patients. 79.0 % of patients at fulvestrant administration had visceral metastases. Regarding best response, in 26.1 % PR was achieved, in 47.8 % of cases SD was recorded, whereas in 26.1 % of patients PD was noted. The median PFS was equal to 5 months. No grade 3 and 4 adverse events were recorded; of note, hot flashes were reported in 18.2 % of male breast cancer patients. Fulvestrant may potentially play a promising role in the optimal therapeutic strategy for male patients with breast cancer diagnosis. However, further clinical and pharmacokinetic investigations are more than warranted before fulvestrant use becomes a common practice in male breast cancer patients. © 2014, Springer Science+Business Media New York.
Keywords: Fulvestant; Hormonal treatment; Male breast cancer; Pooled analysis; therapy